The effect of ripening time on the chemical, textural, volatile and sensorial traits of Bicep femoris and Semimembranosus muscles of the Slovenian dry-cured ham Kraški pršut. (February 2015) - Pugliese, Carolina; Sirtori, Francesco; Škrlep, Martin; Piasentier, Edi; Calamai, Luca; Franci, Oreste; Čandek-Potokar, Marjeta
Abstract: The effect of two ripening times (12 or 16 months) on the chemical, physical, volatile and sensorial properties of Biceps femoris (BF) and Semimembranosus (SM) muscles of Kraški pršut, was studied. Both muscles showed lower water content and higher proteolysis index at 16 than at 12 months. BF had lower lipid contents and higher moisture, salt percentage and proteolysis index than SM. In SM, a decrease of MUFA with time was observed. A higher quantity of total fatty acids was observed for SM than for BF. General increases in hardness, cohesiveness, chewiness and gumminess were observed over time in both muscles. Higher values of force decay coefficient and lower values of hardness, cohesiveness, gumminess and chewiness were found for BF than for SM. Eighty-seven volatile compounds were tentatively identified in both muscles and were more abundant at 16 than at 12 months. Aldehydes were the predominant group followed by acids, alcohols, esters, hydrocarbons, ketones and furans. Highlights: Biceps femoris and Semimembranosus muscles had lower water content and higher proteolysis index at 16 than at 12 months. A decrease of MUFA with time was found in Semimembranosus muscle. An increase in hardness, cohesiveness, chewiness, and gumminess was observed with time. Aldehydes were a predominant group of volatile compounds in both seasoning times. A scarce effect of seasoning time on sensory profile was found.